Peran Sumber Daya Manusia dalam Meningkatkan Kinerja Operasional Bank Konvensional - Aura Maulitha Jatira; Meilani Auliarahma; Andre Nurman Lelo (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
This study aims to describe and analyze the role of human resources (HR) in achieving operational effectiveness in conventional banks. Human resources play a strategic role in ensuring smooth operational activities, service quality, and the achievement of performance targets. This research uses a qualitative descriptive approach through in-depth interviews, observations, and documentation involving operational employees such as tellers, customer service officers, and supervisors at a conventional bank in [mention city, e.g., Yogyakarta]. The collected data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing.The results show that HR plays a crucial role in achieving operational effectiveness through improved employee competence, motivation, discipline, and teamwork. Continuous training and effective communication strengthen employee capabilities and performance. Leadership style and organizational